2020
DOI: 10.1186/s12889-020-08500-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among cyberbullying, parental attitudes, self-harm and suicidal behavior among adolescents: results from a school-based survey in Vietnam

Abstract: Background: The rapid and widespread development of social networking sites has created a venue for an increase in cyberbullying among adolescents. Protective mechanisms and actions must be considered, such as how proximal family factors can prevent self-harm and suicidal behaviors among adolescents exposed to cyberbullying. The present study examined the associations among cyberbullying, parental attitudes, self-harm, and suicidal behaviors after adjusting for confounding factors. Methods: Data were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 41 publications
5
40
1
Order By: Relevance
“…However, this influence decreases during adolescence while conflict peaks, leading to an erosion of parental power and an increased focus on parental psychological control that may impact child-adolescent development [ 7 ]. Results from this study are comparable to studies from other countries, such as India which showed higher levels of poor mental health in children with less parental involvement, and Lebanon, Palestine, Jordan, Syria, and Vietnam which showed that lack of parental understanding was associated with higher incidence of suicidal ideation/thinking [ 18 , 19 , 25 , 30 ]. Those studies also used the GSHS databases for the corresponding countries reporting parental involvement using the same questions utilized in this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…However, this influence decreases during adolescence while conflict peaks, leading to an erosion of parental power and an increased focus on parental psychological control that may impact child-adolescent development [ 7 ]. Results from this study are comparable to studies from other countries, such as India which showed higher levels of poor mental health in children with less parental involvement, and Lebanon, Palestine, Jordan, Syria, and Vietnam which showed that lack of parental understanding was associated with higher incidence of suicidal ideation/thinking [ 18 , 19 , 25 , 30 ]. Those studies also used the GSHS databases for the corresponding countries reporting parental involvement using the same questions utilized in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Studies also showed that decreased emotional resilience led to higher risk of substance use, and that less parental involvement increased overall risks of risky behaviour in later adolescence [ 14 , 35 ]. Furthermore, t having “warm parents, family support, and parental attachment” were significant resilience factors found to be protective against school bullying with adolescents reporting lower levels of loneliness, suicidal ideation and depression especially compared to peer to peer relationships [ 1 , 30 , 36 ]. Existing studies on adolescent high risk behaviour such as substance use, interpersonal violence demonstrated their association with decreased parental involvement and poor mental health, especially among middle and low income countries, however, further studies are needed to explore other contributors to mental health such as nutrition and physical activity [ 17 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…After processing the data, the items to investigate perceptions, attitudes and actions are sufficiently reliable and valid: Cronbach's Alpha = 0.91; Kaiser-Meyer-Olkin Measure of Sampling Adequacy = 0.92. When using the questionnaire survey method, the convention of scores for the questionnaire is shown as follows: Each item has options and is defined by different scores: 1 point: Not important; Not performed, infrequently, unnecessary, unfeasible or weak / poorly performed; 2 points: Implementation is not regular, not necessary, not feasible or done at an average level; 3 points: Important, done regularly, necessary, feasible, or done at a good level [4]. Rating level (by score range): + Level 1: 1.00 ≤ GPA ≤ 1.66: Not important; Not performed, infrequently, unnecessary, unfeasible, or weak / poorly performed.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the present study conducted in Vietnam showed that 9.0% of junior high school students reported their experience of being cyberbullied, and that experience of being cyberbullied was significantly associated with self-harm. In addition, parental acceptance showed a signifi-cant protective relationship by reducing the rates of self-harm and suicidal behaviors, including suicidal ideation, suicidal planning, and suicide attempts in a sample of ado-lescents from Hue city, Vietnam [17]. The research question of this research was what is the form of legal protection for victims of violence against children in elementary schools?…”
Section: Introductionmentioning
confidence: 94%